Correlation of growth and gonadal dysfunction with pre-teenage serum ferritin levels in patients of transfusion dependent beta thalassemia major - Vandana Rani; Sanjeevan Sharma; Rakesh Gupta; Gaurav Mahajan (Wolters Kluwer Medknow Publications, 2019)
Objectives: To compare the growth and gonadal function with pre-teen serum ferritin levels in transfusion dependent β- thalassaemic patients. Materials and Methods: Forty-two transfusion dependent Thalassemia major patients above 15 years age were included in this retrospective study. Their records were analysed which included 6 monthly growth monitoring charts, serum ferritin values from age 9 years to 13 years. Sexual Maturity rating was recorded and the data collected was divided into 4 groups based on presence or absence of growth and gonadal dysfunction. Results: Out of the 42 patients (29 males and 13 females) 14 had both growth and gonadal dysfunction, 10 had only growth retardation, 9 had only gonadal dysfunction and 9 had normal growth and gonadal functions. Mean ferritin values were highest in the first group and least in group with normal growth and gonads. Conclusion: β-Thalassemia major patients have a prolonged life expectancy with adequate transfusion & chelation. Iron overload due to ineffective chelation adversely affects cardiac, hepatic and pituitary function. Anterior pituitary damage due to iron toxicity during early adolescence (9-13 years) impacts the growth and gonadal function of the patient. Intervention at this age may prevent growth and gonadal dysfunction which may not be amenable to therapy at a later stage.